Multicomponent synthesis of chromophores – The one-pot approach to functional π-systems - Brandner, Larissa; Müller, Thomas J. J. (Frontiers in Chemistry, 2023)
Multicomponent reactions, conducted in a domino, sequential or consecutive fashion, have not only considerably enhanced synthetic efficiency as one-pot methodology, but they have also become an enabling tool for interdisciplinary research. The highly diversity-oriented nature of the synthetic concept allows accessing huge structural and functional space. Already some decades ago this has been recognized for life sciences, in particular, lead finding and exploration in pharma and agricultural chemistry. The quest for novel functional materials has also opened the field for diversity-oriented syntheses of functional π-systems, i.e. dyes for photonic and electronic applications based on their electronic properties. This review summarizes recent developments in MCR syntheses of functional chromophores highlighting syntheses following either the framework forming scaffold approach by establishing connectivity between chromophores or the chromogenic chromophore approach by de novo formation of chromophore of interest. Both approaches warrant rapid access to molecular functional π-systems, i.e. chromophores, fluorophores, and electrophores for various applications.